Strengthening The Capacity of Health Cadres Through Active Diabetes Education at The Kagok Health Center, Semarang City, 2025 - Maria Karolina Selano; Oke Dwi Astuti (Journal of Community Engagement in Health, 2025)
Diabetes mellitus (DM) remains a serious health threat in Indonesia and worldwide. The number of people with diabetes is estimated to increase sharply, with around 20.4 million people in Indonesia living with diabetes in 2024. The prevalence of diabetes in Indonesia was around 11.7% in 2023 and continues to rise. The majority of diabetes cases are type 2, which is strongly associated with unhealthy lifestyle factors such as excessive sugar intake, obesity, and lack of physical activity. Health cadres as the spearhead of health services have an important role in educating and assisting DM patients. Based on interviews with the Kagok Health Center, it was found that health cadres have limited knowledge and skills related to diabetes, therefore improvement through training and active education is needed. This community service program aims to increase the capacity of cadres through Active Diabetes education which will be held on June 26, 2025 with interactive and simulation training methods. A total of 80 health cadres participated in the training, whose knowledge improvement was then assessed using valid and reliable questionnaire instruments, with the sampling method employing purposive sampling, which involves selecting samples based on specific criteria relevant to the study objectives. The pre-test and post-test data were analyzed descriptively and statistically using the paired t-test after the Shapiro-Wilk normality test was performed. Results showed a significant increase in the average knowledge score from 40.3% to 75.8% (p < 0.001). Post-training monitoring indicates that cadres are able to implement diabetes education and early detection in a sustainable manner. The program strengthens the role of health cadres in the control of DM at the community level and can be a recommended model of health empowerment for other regions.